Isolated Left Pulmonary Artery Agenesis: A Case Report - Balci, Tansel Ansal; Koc, Zehra Pinar; Kirkil, Gamze; Poyraz, Ahmet Kursad (Galenos Yayincilik, 2012)
Unilateral pulmonary artery agenesis without any cardiovascular malformation is a rare anomaly. We present the imaging findings of a patient who was diagnosed as isolated left pulmonary artery agenesis. A 27-year-old female patient was admitted to our hospital due to dyspnea during exercise for five years. Chest X-ray revealed minimally small left pulmonary hilum and left lung. She was admitted to our clinic with the suspicion of pulmonary artery pathology. Absent perfusion of the left lung with normal ventilation was visualized on scintigraphy. MDCT angiography of pulmonary arteries showed absent left main pulmonary artery with systemic collaterals around left hemithorax. Pulmonary artery agenesis can be asymptomatic and isolated until adulthood. Both scintigraphy and CT angiography images of pulmonary artery agenesis of a patient are rare in the literature. Pulmonary ventilationperfusion scintigraphy can be used not only for pulmonary embolism but also pathologies involving pulmonary artery and its branches.
Keywords: Pulmonary artery; agenesis; ventilation-perfusion scintigraphy; X-Ray computed tomography